Syncephalastrum massiliense sp. nov. and Syncephalastrum timoneanum sp. nov. Isolated from Clinical Samples - Jihane Kabtani; Fatima Boulanouar; Papa Mouhamadou Gaye; Muriel Militello; Stéphane Ranque (Journal of Fungi, 2024)
Mucormycosis is known to be a rare opportunistic infection caused by fungal organisms belonging to the Mucorales order, which includes the Syncephalastrum species. These moulds are rarely involved in clinical diseases and are generally seen as contaminants in clinical laboratories. However, in recent years, case reports of human infections due to Syncephalastrum have increased, especially in immunocompromised hosts. In this study, we described two new Syncephalastrum species, which were isolated from human nails and sputum samples from two different patients. We used several methods for genomic and phenotypic characterisation. The phenotypic analysis relied on the morphological features, analysed both by optical and scanning electron microscopy. We used matrix-assisted laser desorption–ionization time-of-flight mass spectrometry, energy-dispersive X-ray spectroscopy, and BiologTM technology to characterise the proteomic, chemical mapping, and carbon source assimilation profiles, respectively. The genomic analysis relied on a multilocus DNA sequence analysis of the rRNA internal transcribed spacers and D1/D2 large subunit domains, fragments of the translation elongation factor-1 alpha, and the β-tubulin genes. The two novel species in the genus Syncephalastrum, namely S. massiliense PMMF0073 and S. timoneanum PMMF0107, presented a similar morphology: irregular branched and aseptate hyphae with ribbon-like aspects and terminal vesicles at the apices all surrounded by cylindrical merosporangia. However, each species displayed distinct phenotypic and genotypic features. For example, S. timoneanum PMMF0107 was able to assimilate more carbon sources than S. massiliense PMMF0073, such as adonitol, α-methyl-D-glucoside, trehalose, turanose, succinic acid mono-methyl ester, and alaninamide. The polyphasic approach, combining the results of complementary phenotypic and genomic assays, was instrumental for describing and characterising these two new Syncephalastrum species.